Multi-scale input-output analysis for multiple responsibility entities: Carbon emission by urban economy in Beijing 2007 - Guo, Shan; Chen, G.Q. (Journal of Environmental Accounting and Management, 2026)
In ecological accounting for various responsibility entities, embodied ecological endowment fluxes across the local system boundary have different mitigation implications. A framework for the multi-scale input-output analysis is presented in this article to support ecological accounting for mitigation policy making by global, domestic and local responsibility entities. A case study for carbon emissions by the urban economy in Beijing 2007 is made to compare corresponding perspectives. With intensive tertiary industry, the urban economy is revealed as a net carbon emission importer.